Strontium Is Released Rapidly From Agricultural Lime–Implications for Provenance and Migration Studies - Andreasen, Rasmus; Thomsen, Erik (Frontiers in Ecology and Evolution, 2021)
The use of strontium isotopes in prehistoric mobility studies requires accurate isoscapes for evaluating whether prehistoric individuals are local to the areas in which they were buried or not. Isoscapes are often based on modern-day samples, commonly surface waters. There is, however, growing evidence that modern-day farming has a significant impact on the strontium isotopic composition of surface waters and farmed soils, mainly due to the use of agricultural lime for soil improvement. In this paper, we investigate the fate of strontium from agricultural lime in an experimentally-manipulated field in central Jutland, Denmark. Agricultural limestone was added to this field at very high rates in 2012 and 2013 to investigate CO2 storage in soils. Strontium was first measured from the site in 2014. In 2019 we reevaluated strontium concentrations and found that 80-100% of the strontium from the agricultural lime had leached out of the organic-rich topsoil, and likely seeped into the underlying groundwater and nearby surface waters In both the sandy soils of the liming test site and farmed soils and heathland in the adjacent area, Sr exhibits a degree of mobility similar to that of calcium, which is in agreement with data for other soil types and what is predicted by the size of its hydrated ions. Strontium isotopic compositions of unfarmed heathland samples show much higher 87Sr/86Sr ratios, and so are not influenced by carbonates, suggesting that the limestone 87Sr/86Sr signature seen in the farmland and in streams and rivers in contact with this comes from agricultural lime, and not from natural carbonate relicts occasionally found in the area. This suggests that the 87Sr/86Sr signatures of the area were higher in prehistoric times, and that an isoscape map based on samples from modern-day farmland is inappropriate for application to provenance and mobility studies of prehistoric people. Thus, it is critical that the possible impact of farming is evaluated when conducting provenance and mobility studies, especially in areas with Sr-poor soils and where agricultural lime is used for soil improvement. Overlooking this can result in significant overestimation of the degree of prehistoric mobility.